The Legal Framework for Ethical Principles Governing the Conduct of Journalists - Moussaoui, Abdelhalim; Souraya, Bourbaba (Technium Social Sciences Journal, 2022)
Ethical principles refer to a system that guides and dictates journalistic work, media laws and legislation, which determines actions in a particular situation. It is based on personal, professional, social and ethical values and investment in building a system of ethical principles aimed at protecting the integrity of journalists is an investment of great importance. It can contribute to improving the image of journalists and contribute to increasing the chances of success of their press institutions and increase public respect for the profession. At the same time, these standards define the legal responsibilities and duties imposed on journalists, because the purpose of journalism is to achieve respect for human dignity of persons with full and responsible respect for their values, diversity and privacy, and respect for all the requirements of protecting public order. On the other hand, national legislation requires a journalist to adhere to the ethical principles governing the conduct of journalists, and it is obvious that these principles are behaviors that characterize a journalist